The one constant: A causal effect of collective bargaining on employment growth? Evidence from German linked-employer-employee data - Tobias Brändle; Laszlo Goerke (Institut für Angewandte Wirtschaftsforschung (IAW), 2015)
A large number of articles have analysed 'the one constant' in the economic effects of trade unions, namely that union bargaining reduces employment growth by two to four percentage points per year. Evidence is, however, mostly related to Anglo-Saxon countries. We investigate whether a different institutional setting might lead to a different outcome, making the constant a variable entity. We use linkedemployer-employee data for Germany and analyse the effect of collective bargaining coverage on employment growth in German plants. We find a robust and negative correlation between being covered by a sector-wide bargaining agreement or firmlevel contract and employment growth per annum of about 0.8 percentage points. Using various approaches, however, we cannot establish a causal interpretation of the effects, suggesting that the cross-section results are driven by selection.
Keywords: J23; J52; J53; J63; 330; collective bargaining; employment growth; job flows; trade unions